Pendampingan dan Pembuatan Kaki Palsu (Prosthesis) Bersama SRC Holland - Lukita, Chandra; Chandra, Aditya Kurniawan; Laily Purnamasari, Dewy; Asfi, Marsani; Amroni, Amroni; Hatta, Muhammad; Norhan, Linda; Suwandi, Suwandi (Penerbit Goodwood, 2023)
Purpose: make a positive contribution to society, especially in terms of health and rehabilitation for individuals who require prostheses. This community service can include direct assistance to individuals who need prosthetic limbs as well as providing training and mentoring. Methodology: The method of this service activity is identifying people who need prosthesis assistance, establishing collaboration with SRC Holland, developing a mentoring program, making prosthetic limbs, evaluating and monitoring. Results: The result of International Community Service is the birth of assistance and free manufacture of prosthetic limbs that are needed, so that this international community service activity is able to help physically disabled people overcome their shortcomings. Limitation: The limitation of this community service activity was the limited time for the Dutch SRC Holland team's visit to Indonesia, resulting in less than optimal activity time. Contribution: This research makes a significant contribution to people with disabilities by providing assistance services and making prosthetic limbs for free. This can provide a real solution for individuals who need prosthetic devices but have financial limitations.